Propuesta técnica para el manejo de residuos sólidos municipales de la localidad de Habana - Campos Chumbe, Gustavo Adolfo (2016)
With the implementation of this research work enables us to reach succinctly to the following, is ,achievement have a current Situational diagnosis of the municipal waste management from the locality, likewise allows us to know sorne basic characteristics of the locality, as well as which allowed us to know the socio-economic activities more aspects of the Habana district, to know its possible zones or places of Final disposition of Salid Residues, the same thing also implies having possibilities of working as a whole with the nearest districts since it is the case of Soritor and Calzada district, whenever its proximity in terms of distance there is the potential to work so set the lntegrated Management of Municipal Salid Waste of competition. " Any technical proposal for salid waste management models involves the • generation, storage, collection, transportation and disposal of salid waste; when these wastes are not treated properly, almost always they end up as garbage dumps in the streets and public places which impairs the beautification and quality of life of the population. There was also a Current Situational diagnosis of Domestic Waste production and sorne potential sources of waste generation, and which also sorne possibilities for recycling and reuse are. On the other hand, there are people who live with pi les of garbage and this is a reality . at the level of the entire region. lt is important to take more interest in sorne of the phases or stages of the whole life cycle of Salid Waste, lt mean in this present research phase: Collection Transport and Disposal of Salid Waste generated in the Habana district , so that good serve for making better decisions of municipal management district. Key words: sol id waste management, recycling and reuse.